THE EFFECT OF LIVE STREAMING AND ONLINE CUSTOMER REVIEW ON THE PURCHASE DECISION OF HANA FASHION PRODUCTS IN TIKTOK SHOP WITH CONSUMER TRUST AS AN INTERVENING VARIABLE - Merlinna; Lysa Tantria; Fitrianingsih; Imelda Mardayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of live streaming and online customer reviews on purchasing decisions for Hana Fashion products at TikTok Shop with consumer trust as an intervening variable. The research method used is a quantitative approach with data collection through an online questionnaire from 96 respondents who have made purchases at the store. Data analysis was carried out using SmartPLS 3.0 software. The results of the study showed that live streaming and online customer reviews had a significant effect on purchasing decisions. Online customer reviews were also shown to have a positive effect on consumer trust, but consumer trust did not have a significant effect on purchasing decisions and was unable to mediate the relationship between the two independent variables and purchasing decisions. These findings indicate that although trust is important in a digital context, purchasing decisions at TikTok Shop are more influenced by visual content and direct reviews from other users. Therefore, business actors need to optimize live streaming and customer review strategies in increasing purchasing decisions on social media-based e-commerce platforms.